Evaluation and development of conceptual document similarity metrics with content-based recommender applications - Gouws, Stephan (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.